Short Communication: Proportion faunal assemblage of rodents in geoecological districts of Mordovia, Russia - Alexey Andreychev Alexey (Society for Indonesian Biodiversity, 2020)
Abstract. Andrechev A. 2020. Short Communication: Proportion faunal assemblage of rodents in geoecological districts of Mordovia, Russia. Biodiversitas 21: 3961-3968. In one natural area, animals may have different distribution. In some areas they inhabit, and in other areas, they do not inhabit. Scientists have been working on this issue for a long time. In this study reports that the species composition and distribution of species varies depending on geoecological districts. Twenty-eight rodent species have been recorded in the territory of Mordovia. The largest number of species in the region belongs to those living in coniferous and broad-leaved forests (42.9%). In the second place in terms of representation are species widely distributed in several natural areas (28.5%). They are slightly inferior to the types of steppe fauna (25%). The taiga type of fauna is represented by only 3.6% of the total number of registered species. For each geoecological district, the features of the rodent fauna are given and rare species are identified. The forest-steppe region of Mordovia is compared in rodent fauna with other regions of Russia with different typical faunal assemblages.